The Influence of Human Resource Quality, Budget Planning, and Regulation on Budget Absorption with Internal Control System as a Moderating Variable - Fadhila Aurelia; Endah Susilowati (Universitas Muhammadiyah Tangerang, 2026)
This study aims to analyze the effect of human resource quality, budget planning, and regulation on budget absorption, with the internal control system serving as a moderating variable. The research employs a quantitative approach with an explanatory design to examine the causal relationships among the variables. Data were collected through questionnaires distributed to government employees involved in the process of budget preparation and implementation. A purposive sampling technique was applied to ensure that the selected respondents were relevant to the research objectives. The final sample size met the requirements for analysis using the SEM-PLS method. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The findings reveal that human resource quality, budget planning, and regulation have positive and significant effects on budget absorption. Meanwhile, the internal control system does not show a significant direct effect on budget absorption. In addition, the internal control system is not proven to moderate the relationship between human resource quality, budget planning, and regulation with budget absorption. The research model explains 42.8% of the variance in budget absorption. These results indicate that organizational capacity factors, particularly employee competence and the quality of planning, play a more dominant role than control mechanisms in improving budget realization. Therefore, strengthening staff capacity and enhancing the quality of budget planning processes are important strategies for improving public financial management performance.